2017
DOI: 10.1007/s10669-017-9632-y
|View full text |Cite
|
Sign up to set email alerts
|

A multi-objective location-allocation optimization for sustainable management of municipal solid waste

Abstract: Abstract:The location problem of treatment and service facilities in municipal solid waste (MSW) management system is of significant importance due to the socio-economic and environmental concerns. The consideration of waste treatment costs, environmental impact, greenhouse gas (GHG) emissions, social fairness as well as other relevant aspects should be simultaneously taken into account when a MSW management system is planned. Development of sophisticated decision support tools for planning MSW management syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(15 citation statements)
references
References 49 publications
0
15
0
Order By: Relevance
“…(2016) × × × × × Case study Yu and Solvang (2016) × × × × × × Numerical experiment Zhao et al. (2016) × × × × × × × Case study Yu and Solvang (2017a) × × × × × × Numerical experiment Asgari et al. (2017) × × × × × × Case study Farrokhi-Asl et al.…”
Section: Literature Reviewmentioning
confidence: 99%
“…(2016) × × × × × Case study Yu and Solvang (2016) × × × × × × Numerical experiment Zhao et al. (2016) × × × × × × × Case study Yu and Solvang (2017a) × × × × × × Numerical experiment Asgari et al. (2017) × × × × × × Case study Farrokhi-Asl et al.…”
Section: Literature Reviewmentioning
confidence: 99%
“…By considering the environmental, economic, and social objectives, Ramos et al discussed the planning decisions of reverse logistics systems. With balancing the trade‐off among environmental influence and system operating costs, Yu and Solvang presented a multi‐objective location‐allocation model from the perspective of network design. Although these models extend the conventional facility location problem to the situation of taking the economic and environmental criteria simultaneously, they neglect the uncertainty factors related to the customers' demands and the transportation costs.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Yu and Solvang used multi-objective location-allocation for the management of municipal solid waste, but the capacity constraint was omitted, and their results showed that the CPU running time increased significantly with an increase in the size of the problem. For future development, they proposed using an efficient algorithm such as a genetic algorithm [16]. Ma and Zhao used a multi-objective artificial immune optimization model in land use allocation.…”
Section: Introductionmentioning
confidence: 99%